2010
DOI: 10.1007/s10915-010-9444-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Instabilities in Well-Balanced Finite Volume Schemes for Frictional Shallow Water Equations. The Kinematic Wave Case

Abstract: We report the developments of hydrodynamic instabilities in several wellbalanced finite volume schemes that are observed during the computation of the temporal evolution of an out-balance flow which is essentially a kinematic wave. The numerical simulations are based on the one-dimensional shallow-water equations for a uniformly sloping bed with hydraulic resistance. Subsequently, we highlight the need of low dissipative high-order well-balanced filter schemes for non-equilibrium flows with variable cut-off wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…1. In the present study, we use closure equations for λ and κ consistent with (15). The key problem is that the available data do not allow us to fit all of the parameters.…”
Section: Closure Equationsmentioning
confidence: 99%
See 4 more Smart Citations
“…1. In the present study, we use closure equations for λ and κ consistent with (15). The key problem is that the available data do not allow us to fit all of the parameters.…”
Section: Closure Equationsmentioning
confidence: 99%
“…However, numerical simulations of free surface instabilities in frictional flows down inclined planes have shown that a non-negligible eddy viscosity ν is required to avoid the development of unphysical short wavelength instabilities as well as to reproduce the non-linear steady-state shape of roll waves [11,15,18,64]. In this study the main role of the eddy viscosity is to prevent the development of discontinuities in the free surface, which allows us to evaluate the free surface slope in the presence of jumps and steps of the bed elevation.…”
Section: Closure Equationsmentioning
confidence: 99%
See 3 more Smart Citations